Investigating Perceived Stress and Quality of Life Among Pharmacy Students: A Systematic Review - Dhea Ananda Fitri; Susi Ari Kristina; Quang Trung Vo (Fakultas Psikologi, Universitas Putra Indonesia YPTK Padang, 2026)
Pharmacy students experience substantial stress due to demanding academic requirements, competitive educational environments, and challenges associated with transitioning into professional roles, which may negatively affect their quality of life. This systematic review aims to examine the relationship between perceived stress and quality of life among pharmacy students and to identify key stress determinants influencing their well-being. Eligible studies focused on pharmacy students, used validated instruments to measure perceived stress and quality of life, and were published between 2020 and 2024. A total of 1,040 records were identified through database searching, of which 12 studies met the inclusion criteria after screening. Two additional studies were identified through manual searching, resulting in 14 studies included in the review. The findings indicate that academic workload, financial pressure, limited social support, and concerns about transitioning into professional practice are the main contributors to perceived stress, which in turn negatively impacts students’ quality of life. Commonly used assessment tools included the Perceived Stress Scale and the Short Form-12 Health Questionnaire. This review highlights the significant impact of perceived stress on the quality of life of pharmacy students and underscores the need for targeted stress management interventions to support their well-being.